2011
DOI: 10.1111/j.1365-2109.2010.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ration level on growth, nitrogenous excretion and energy budget of juvenile yellow catfish, Pelteobagrus fulvidraco (Richardson)

Abstract: Growth, nitrogenous excretion and energy budget of juvenile yellow cat¢sh, Pelteobagrus fulvidraco (initial body weight 1.17 AE 0.28 g) at various levels (50%, 60%, 70%, 80%, 90% and 100% satiation per day) were investigated with feeding diet containing 40% protein. Speci¢c growth rate of yellow cat¢sh increased (2.79^3.34% day) signi¢cantly (Po0.05) with ration level (RL) increasing. Feed conversion e⁄ciency, feed protein retention e⁄ciency and feed energy retention e⁄ciency increased with the increase in RL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The excessive feeding level induced fat accumulation and histopathological lesions in the liver of GIFT fry, which provided additional evidence that the high feeding rate was suboptimal. Whole-body proximate composition of fish has been used to indicate fish quality and determine the optimum frequency and rate for feeding (Zhang et al 2011). Feeding rates FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
“…The excessive feeding level induced fat accumulation and histopathological lesions in the liver of GIFT fry, which provided additional evidence that the high feeding rate was suboptimal. Whole-body proximate composition of fish has been used to indicate fish quality and determine the optimum frequency and rate for feeding (Zhang et al 2011). Feeding rates FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
“…Feces were siphoned 2 hr after feeding, dried to constant weight and then weighed for use according to Zhang et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative feed was soaked in water for 1 hr, then siphoned, dried, and weighed in order to estimate the remnant recovery and to adjust the food ingestion. Feces were siphoned 2 hr after feeding, dried to constant weight and then weighed for use according to Zhang et al (2011).…”
Section: Experiments Designmentioning
confidence: 99%
“…Within the optimum feeding rate range, there is a significant linear relationship between the feeding rate and the growth rate, and fish growth tends to stabilize or decline when the feeding rate is above the optimum (Zhang et al . ). Numerous studies of fish have shown that increasing the feeding frequency can promote growth to a certain extent, but beyond a certain range, there is no obvious promotional effect (Dwyer et al .…”
Section: Factors Influencing Fish Feedingmentioning
confidence: 97%